Human resources management - French, Wendell L., 1923- (Houghton Mifflin, 1998)
An overview of Human Resources Management. Organizational Considerations in Human Resources management. Job Design and Staffing. Development and Appraisal. Compensation and Reward. Employee protection and representation. Participation, Globalization, and the future of HRM.